Pengkajian Penerapan Prinsip Iktikad Tidak Baik dalam Pendaftaran Merek pada Sengketa Merek Jaguar - Muhammad Alfian Prasetyo; Rika Ratna Permata; Ranti Fauza Mayana Tanwir (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This study analyzes the application of the principle of bad faith in the trademark registration process, especially in the Jaguar trademark dispute between PT Surabaya Top and Hence Teh. Through descriptive analysis research with a normative juridical approach, the results of this study indicate a violation of the principle of bad faith from trademark registration carried out by Hence Teh because it fulfills the principle of bad faith which is studied in accordance with the Trademark and Geographical Indications Law.